134k views
2 votes
Please help me and explain how do I rearrange this equation to become y=mx+b form? THANKS!!!​

Please help me and explain how do I rearrange this equation to become y=mx+b form-example-1
User Pompeyo
by
5.0k points

2 Answers

4 votes
Here you go, hope this helps!
Please help me and explain how do I rearrange this equation to become y=mx+b form-example-1
User SaiBot
by
5.6k points
5 votes

Answer:

Explanation:

3x - 2y = 9

Rearrange

3x - 9 = 2y

2y = 3x - 9

Divide both sides by 2

y = 3x/2 - 9/2

y = (3/2)x - 9/2 or y = (3/2)x + (-9/2)

Where m= 3/2 and b= -9/2

User Xjmdoo
by
5.3k points